Optimalisasi Strategi Pengendalian Akar Pohon untuk Mencegah Kerusakan Perkerasan di Banda Aceh - Ria Purnama; Sahlan Zuliansyah; Sri Batara; Nurfajri Arisaputri (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
Damage to urban infrastructure such as roads, sidewalks, and drainage systems caused by tree root growth has become a significant challenge in the development of infrastructure and green open spaces in developing cities like Banda Aceh. This study aims to identify urban infrastructure damage related to tree roots, as well as strategies for tree planting and maintenance, particularly related toroot control, that can address these issues. The employed methods include field observations and documentation at fewurban locations experiencing pavement damage, as well as literature review and analysis of proven root management practices that consistently and comprehensively solve these problems.